MEASURES OF COUNTERACTION OF LATENTIZATION OF CRIME - Syzdykov Тимур Жагипарович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2023)
The urgency of the given problem is caused by specificity studying latentis criminality and minimization of negative consequences.Decreasinglatentis crimes depends on reliability of criminological indicators.